2019
DOI: 10.1093/humrep/dez202
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive and behavioural outcome of children born after IVF at age 9 years

Abstract: STUDY QUESTION Do ovarian stimulation (OS) and the in vitro laboratory procedures affect offsprings’ cognitive and behavioural outcome at 9 years? SUMMARY ANSWER OS and the in vitro laboratory procedures or the combination of both were not associated with cognitive and behavioural outcome at age 9 years. WHAT IS KNOWN ALREADY ART is not associated with an adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…We previously demonstrated that the in vitro fertilization-procedures did not affect developmental outcome at 9 years. 11,12 Therefore, we pooled the ART-subgroups to form one study group. The group included singletons and twins (Table 1 and Table S1, online supporting information).…”
Section: Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that the in vitro fertilization-procedures did not affect developmental outcome at 9 years. 11,12 Therefore, we pooled the ART-subgroups to form one study group. The group included singletons and twins (Table 1 and Table S1, online supporting information).…”
Section: Methods Participantsmentioning
confidence: 99%
“…In brief, the participants were born after in vitro fertilization or intracytoplasmic sperm injection, with or without ovarian stimulation, or conceived naturally to couples with reduced fertility. We previously demonstrated that the in vitro fertilization‐procedures did not affect developmental outcome at 9 years 11,12 . Therefore, we pooled the ART‐subgroups to form one study group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ART however does not seem linked to an increase in the risk of autism spectrum disorder or preeclampsia ( Diop et al , 2019 ; Kennedy et al , 2019 ). Only frozen embryo transfer was associated with a small yet statistically significant increased risk for childhood cancer ( Hargreave et al , 2019 ), and the cognitive, behavioural and school performance of children born from IVF versus ICSI remain comparable ( Heineman et al , 2019 ; Norrman et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%